PENGEMBANGAN MEDIA INTERAKTIF BERBASIS DEEP LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI STATISTIKA - Jonerri Dikens; Jamilah; Dewi Risalah (STKIP Subang, 2026)
This study aims to develop interactive learning media based on deep learning (conscious, meaningful and enjoyable) towards students' mathematical problem-solving abilities in statistics material for class VIII of SMP Negeri 1 Toho. This study is a Research and Development (R&D) research and development using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques are in the form of indirect communication techniques and measurement techniques, with research instruments in the form of expert validation sheets, practicality questionnaires, pretest and posttest questions. The research sample is class VIII C consisting of 25 students. Data analysis techniques used include validity, practicality, effectiveness and influence analysis. The results of the study indicate that the developed interactive learning media achieved the category of very valid with a validity percentage of 92%, very practical with a practicality percentage of 91.5%, and effective with an effectiveness percentage of 76%. The paired t-test results showed that > (62.574 > 2.064). Therefore, H₀ was rejected and H₁ was accepted, indicating a significant effect on mathematical problem-solving ability before and after the media was implemented. Thus, interactive learning media based on deep learning (conscious, meaningful, and enjoyable) is suitable for use in mathematics learning processes in schools.